Physical and mechanical properties of wood composite from oil palm (Elaeis guineensis Jacq.) fronds - Abd Ghani, Muhammad Aizat; Alamjuri, Roziela Hanim; Wahab, Razak; Mat Rasat, Mohd Sukhairi; Ashaari, Zaidon (Faculty of Forestry, Universiti Putra Malaysia, 2013)
This study involves the production of wood composite from oil palm fronds (OPF). The aim was to determine the wood composite properties fabricated from three different OPF sections, i.e., bottom, middle and top sections bonded with either phenol formaldehyde (PF) or urea formaldehyde (UF). The results showed that regardless of the type of adhesive used, the wood composite fabricated from the bottom section of OPF produced the best quality properties followed by those fabricated at the middle and top sections. The properties of PF-bonded composites were superior compared to UF-bonded composites. The potential use of OPF as an alternative raw material in the wood-based industries is good.